1999
DOI: 10.1103/physrevlett.82.3839
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Adatom Motion under the Influence of Mutual Interactions:O/Ru(0001)

Abstract: The diffusive motion of O atoms adsorbed on Ru(0001) was observed on the atomic scale by scanning tunneling microscopy with temporal resolution of ഠ10 ms at room temperature. From statistical analysis of the changes of the atom configurations in sequences of more than 1000 images, mean residence times of oxygen atoms in the neighborhood of other oxygen atoms were extracted. The residence times vary by more than 1 order of magnitude over distances of three lattice constants, indicating the necessity of includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
2
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 15 publications
3
59
2
1
Order By: Relevance
“…Also two types of adsorption sites were included, namely, the hcp-and fcc-hollow site, and also interactions between the O atoms in these two types of hollow sites were included up to third neighbor distances. The calculated interaction parameters agree well with those determined recently from STM studies [37]. Quantitative information on adsorbate-adsorbate interactions have also been obtained for nitrogen on Fe(1 0 0) from STM investigations [38].…”
Section: Surface Phase Transitions and Thermal Desorptionsupporting
confidence: 76%
“…Also two types of adsorption sites were included, namely, the hcp-and fcc-hollow site, and also interactions between the O atoms in these two types of hollow sites were included up to third neighbor distances. The calculated interaction parameters agree well with those determined recently from STM studies [37]. Quantitative information on adsorbate-adsorbate interactions have also been obtained for nitrogen on Fe(1 0 0) from STM investigations [38].…”
Section: Surface Phase Transitions and Thermal Desorptionsupporting
confidence: 76%
“…In the past, information on diffusion of gas species has mainly been obtained from macroscopic diffusion experiments [1], in which the measured diffusion constant, derived through Fick's law, is in general an average over different diffusion processes. Recently, it has been demonstrated that microscopic information on surface diffusion of gas species can be obtained using scanning tunneling microscopy (STM) to track the position of individual adatoms on single crystal surfaces [2][3][4][5].…”
Section: (Received 13 January 2000)mentioning
confidence: 99%
“…The values of the pre-exponential m 0 and of the energy barrier have now been determined for several systems [17][18][19][20].…”
Section: Selected Experimental Resultsmentioning
confidence: 99%